Diagnosing and treating depression in epilepsy. (January 2017) - Elger, Christian E.; Johnston, Samantha A.; Hoppe, Christian
Highlights: Literature on depression in epilepsy is selectively reviewed. Diagnosing depression entitles patients for professional support. Psychotherapy has proven its efficacy in ten adequate clinical trials. Due to lack of adequate studies, efficacy of antidepressants remains unclear. Abstract: At least one third of patients with active epilepsy suffer from significant impairment of their emotional well-being. A targeted examination for possible depression (irrespective of any social, financial or personal burdens) can identify patients who may benefit from medical attention and therapeutic support. Reliable screening instruments such as the Neurological Disorders Depression Inventory for Epilepsy (NDDI-E) are suitable for the timely identification of patients needing help. Neurologists should be capable of managing mild to moderate comorbid depression but referral to mental health specialists is mandatory in severe and difficult-to-treat depression, or if the patient is acutely suicidal. In terms of the therapeutic approach, it is essential first to optimize seizure control and minimize unwanted antiepileptic drug-related side effects. Psychotherapy for depression in epilepsy (including online self-treatment programs) is underutilized although it has proven effective in ten well-controlled trials. In contrast, the effectiveness of antidepressant drugs for depression in epilepsy is unknown. However, if modern antidepressants are used (e.g. SSRI, SNRI, NaSSA), concerns about an aggravation of seizures and or problematic interactions with antiepileptic drugs seem unwarranted. Epilepsy-related stress ("burden of epilepsy") explains depression in many patients but acute and temporary seizure-related states of depression or suicidality have also been reported. Limbic encephalitits may cause isolated mood alteration without any recognizable psychoetiological background indicating a possible role of neuroinflammation. This review will argue that, overall, a bio-psycho-social model best captures the currently available evidence relating to the etiology and treatment of depression as a comorbidity of epilepsy.